2009
DOI: 10.1021/la803871z
|View full text |Cite
|
Sign up to set email alerts
|

Living Fungi Cells Encapsulated in Polyelectrolyte Shells Doped with Metal Nanoparticles

Abstract: We report the layer-by-layer coating of living fungi cells (Saccharomyces cerevisiae and Trichoderma asperellum) with polyelectrolytes poly(allylamine hydrochloride)/sodium poly(styrene sulfonate) and bovine serum albumin/DNA and citrate-stabilized gold and silver nanoparticles. It was found that the nanoparticles were effectively incorporated between oppositely charged polyelectrolyte layers, modifying the topography and the roughness of cell walls. The formation of large aggregates of nanoparticles on the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 39 publications
2
72
0
Order By: Relevance
“…Organic polymers and inorganic nanoparticles can bring various new functionalities to the cell membranes, including fluorescent and magnetic property, catalytic moieties, and supporting templates. [11][12][13][14][15][16][17][18][19] For that, we have attempted to assemble multilayers on the yeast cells with a combination of GO nanosheets with two most common strong polyelectrolytes such as PDDA þ , and PSS -. According to the same protocol, the yeast cells were encapsulated based on the electrostatic interactions between oppositely charged GO nanosheets and organic polyelectrolytes in a format of yeast@(PDDA þ /GO-COO -) and yeast@(GO-NH þ 3 / PSS -), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic polymers and inorganic nanoparticles can bring various new functionalities to the cell membranes, including fluorescent and magnetic property, catalytic moieties, and supporting templates. [11][12][13][14][15][16][17][18][19] For that, we have attempted to assemble multilayers on the yeast cells with a combination of GO nanosheets with two most common strong polyelectrolytes such as PDDA þ , and PSS -. According to the same protocol, the yeast cells were encapsulated based on the electrostatic interactions between oppositely charged GO nanosheets and organic polyelectrolytes in a format of yeast@(PDDA þ /GO-COO -) and yeast@(GO-NH þ 3 / PSS -), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The layer-by-layer (LbL) self-assembly of polymers also has been used for encapsulating individual living cells with organic macromolecules. [3][4][5][6][7][8][9] In addition, the surface of microbial cells was doped with various nanoparticles, such as silica, [10,11] gold, [12] silver, and iron, [13] and carbon nanotubes [14] by the LbL self-assembly. Very recently, individual yeast cells were encapsulated within silica, [15,16] calcium phosphate, [17] calcium carbonate, [18] and polydopamine, [19] inspired by biomineralization processes or an adhesive protein found in mussels.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms, including viruses, bacteria, and fungi, grow in unique and interesting structures that can be combined with the functional properties of noble metal nanoparticles to generate new smart materials [13,16,22,23]. Usually, it is necessary to modify the surface of nanoparticles in order to increase their affinity for the mycelium [47]. However, in this study, we successfully exposed the fungi directly to colloidal suspensions of unmodified gold and silver nanoparticles, resulting in a stable hybrid material [22].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, studies have demonstrated X-ray µCT identification of Gram-negative bacteria using silver microspheres as a contrast agent , and multispecies water biofilms using barium sulfate and propidium iodide (Davit et al, 2011). Other studies have also used gold and silver nanoparticles to identify yeast species by surface-enhanced Raman scattering (Fakhrullin et al, 2009), highlighting that these contrast stains, combined with X-ray µCT, are applicable across a wide range of potential pathogens. Importantly, also for clinical application, silver and gold nanoparticles also lend themselves to conjugation with oligonucleotides, which may allow bacterial-specific labelling capable of resolving bacteria from thrombus and other occlusions, which future studies into clinical application will need to address (Tauran et al, 2013).…”
Section: Discussionmentioning
confidence: 99%